Exploring the intersections of creative and academic life among Australian academic creative writing practitioners. Issue 3 (1st September 2016) - Strange, Shane; Hetherington, Paul; Eaton, Anthony
ABSTRACT: Recent literature on the activities of creative practitioners within the academy has focused on their roles as cultural workers within the higher education sector – contributing to the so-called 'creative economy' as skills-based practitioners with 'real world' experience – or it has considered the role of the academic teacher in shaping the creative life and careers of their students. Relatively little has been done, however, to specifically examine the lived experience of creative writers in the Australian academy as they attend to the professional requirements of their work as teaching and research academics on the one hand, and their linked professional activities as creative writers, on the other. This paper reports on the findings from a preliminary survey conducted between July and August 2013 which aimed to explore the career trajectories, expectations and experiences of work at the nexus of creative and academic labour. It identifies a number of key tensions between academic and creative aspirations of academics who are creative writers, along with institutional benefits that in some cases aided the production of their creative work.